The Impact of NGOs’ Services on Women Empowerment in Bahir Dar, Ethiopia - Mulugeta, Sofanit; Hailu, Fesseha (Ethiopian Journal of Social Sciences, 2018)
Women empowerment issues perceived nationally or locally are being addressed by both state and non-state agencies. Beside the government intervention, NGOs are implementing various types of Women Empowerment Programs. In this paper an attempt has been made to shed light on the effectiveness of NGO’s functions on women’ s empowerment in Bahir Dar town. A cross-sectional survey  research  design was employed to address the research objectives . The respondents were selected using  simple random sampling technique  from three NGOs working on women’s empowerment in Bahir Dar city; namely, Care Ethiopia, Mums for Mums and Catholic Women’s Training Center. This study measures women’s empowerment at two levels: individual and collective (community) empowerment on four dimensions; (economical, socio-cultural, familial/interpersonal and psychological dimensions). Findings indicate that NGOs were effective on women’s empowerment programs on saving and credit service functions with (M=129.80, SD=12.56), followed by social development and vocational training services (M=127.11, SD=11.39). The study emphasizes the need for NGOs to organize and integrate their activities to effectively address the problem of women in Bahir Dar city.